STATE ADMINISTRATIVE LEGAL REVIEW ON THE BILL OF RETRACTION LAW OF CORRUPTED ASSETS IN ERADICATION EFFORT OF CORRUPTION IN INDONESIA - Simatupang, Dian Puji (Indonesia Law Review, 2011)
Since eradicating corruption having been continously encouraged by late governments – and until now – , there would not be less important as to retracting the corrupted assets. There are many aspects to be considered in doing such action, such as manifesting the legal aspects of administrative law, and so other applied national regulations. By these regulations, such as Law No. 7 of 2006 on Ratification of United Nations Convention against Corruption, 2003 (Konvensi Perserikatan Bangsa Bangsa Anti-Korupsi, 2003), Law Number 25 of 2003 On Amendment to Law Number 15 of 2002 on Money Laundering, Act 30 of 2002 on Corruption Eradication Commission, Law Number 20 Year 2001 regarding Amendment to Law Number 31 Year 1999 on the Eradication of Corruption, and Government Regulation Number 65 of 1999 on Implementation Procedures for Examination of State Property, retraction the corrupted assets should be define in order to get known about eradicating corruption. Another issue that urgently to be defined, as it also become main subject of retracting assets, is the asset itself. Indeed, as the asset which become mainly discussed about is State assets. So, it would be very necessary to clearly have a distinction between State responsibility and that of irresponsibility of the State, in order to settle down, as an after effect, many interpretations.